Pelatihan Kemampuan Asesmen Diagnostik Learning Style Dalam Meningkatkan Performance Guru BK Pada Kurikulum Merdeka - Wahyuni, Hera; Nelyahardi, Nelyahardi; Yulianti, Yulianti; Sarman, Freddi; Rahmayanty, Dinny (Jambura Arena Pengabdian, 2023)
Diagnostic assessment skills training for SMPN guidance and counseling teachers at the Muaro Jambi Education and Culture Service aims to provide skills and understanding about the use of diagnostic assessment, one of which is learning style. The results of this activity include: increasing the insight and skills of guidance and counseling teachers in using diagnostic assessments in guidance and counseling services. The understanding and skills of guidance and counseling teachers in applying diagnostic assessments develop so that they can assist in implementing guidance and counseling activities in schools.